P3.039 Earlier Menarche is Associated with a Higher Prevalence of Herpes Simplex Type-2 (HSV-2) in Rural Malawi. (13th July 2013) - Glynn, J R; Kayuni, N; Gondwe, L; Price, A; Crampin, A C
Abstract : Background: We have previously shown that girls with earlier menarche tend to have sexual debut and marry at a younger age, and to drop out of school earlier. We investigated the association between menarche and HSV-2 infection. Methods: The Karonga Prevention Study in northern Malawi includes demographic surveillance in a population of about 33, 000. Information on sexual behaviour was collected in annual rounds from 2007 and serosurveys for HSV-2 were done. A question on age at menarche for women aged 15–30 was added midway through the first sexual behaviour round. For those with missing data on age at menarche from the first round the response from the subsequent round was used. Results: 6796 women were interviewed, 86% of those eligible. This included 3965 women aged 15–30: 3419 (86%) were tested for HSV-2 and 870 were positive (25.5%). 3166 reported age at menarche: approximately one quarter had menarche aged < 14, 14, 15 and ≥ 16. After adjusting for current age, there was a strong correlation between older age at menarche and lower prevalence of HSV-2: compared to those with menarche aged < 14, the age-adjusted odds ratios were 0.89 (95% CI 0.71–1.1), 0.71 (0.57–0.89) and 0.69 (0.54–0.89) for menarche aged 14, 15 and ≥ 16 respectively. This association persisted after adjusting for socio-economic factors, including schooling, and for proximal risk factors (marital status, age at first sex, lifetime number of partners). Conclusion: In this population earlier menarche appears to lead to multiple disadvantages. Since the association with HSV-2 persisted after adjusting for measured sexual behaviour factors this suggests that early menarche leads to riskier behaviours not captured in our survey, for example having higher risk partners. Age at menarche is likely to drop with improving nutrition, putting more young women at risk.